Brain Hemisphericity, Creative Thinking and Critical Thinking of Malaysian Science and Arts Students - Chua, Yan Piaw (2002)
The purposes of this study were: (1) to explore the nature of brain hemisphericity, creative thinking and critical thinking abilities of Malaysian students, (2) to compare brain hemisphericity, creative thinking and critical thinking abilities of the students in terms of academic major, gender and ethnicity variables, and (3) to ascertain the relationships between brain hemisphericity and creative thinking; and between brain hemisphericity and critical thinking . The subject of this study consisted of 216 form-six students (109 science major and 107 arts major) from twenty-seven secondary schools of the state of Selangor. Three instruments were used to appraise brain hemisphericity, creative thinking and critical thinking. The instruments were Your Styles of Learning and Thinking. Torrance Tests of Creative Thinking and Watson-Glaser Critical Thinking Appraisal. The results demonstrated that the majority of the students were right hemisphere dominants, and they preferred to use only one of their hemispheres in learning and thinking (right hemisphere 54.6%, left hemisphere 36.6%, and whole brain 8.8%). Descriptive analysis o n creative thinking abilities indicated that the students were relatively fluent in producing ideas, and the ideas they created were likely to be original. However, they have less ability to evaluate and elaborate the ideas creatively, and tend to leap to the conclusions about the ideas they create prematurely.